Investigating the inter-country variations in game interruptions across the Big-5 European football leagues - Zhao, Y.; Zhang, H. (International Journal of Performance Analysis in Sport, 2021)
This paper reports an empirical investigation of game interruptions in competitions based on data from the European Big-5 leagues. The results showed that 1) visiting teams and teams facing strong opponents tended to have longer game interruptions; 2) the durations of throw-ins and stoppages due to out-of-bounds balls were significantly longer in the English Premier League than in the other four leagues (p < 0.001), and the durations of free kicks were longer in the English Premier League than in three other leagues (except Ligue 1, p < 0.001); 3) the durations of free kicks (p < 0.001), throw-ins (p = 0.038) and goal kicks (p < 0.001) increased towards the end of matches, but the durations of interruptions related to free kicks (p < 0.001) in the offensive zone decreased significantly as the end of the game approached; and 4) the durations of many interruptions served strategic purposes, as, for example, the time spent by a one-goal leading team on throw-ins (p < 0.001), goal kicks (p < 0.001), corner kicks (p < 0.01) and free kicks (p < 0.01) increased with game time, while for one-goal trailing teams, the time spent on these interruptions decreased over time (all p < 0.001).